Answer: the answer is (2,-4) if that's not the answer then can u post a full picture of the question
Step-by-step explanation:
3x - y + z = 5 . . . (1)
x + 3y + 3z = -6 . . . (2)
x + 4y - 2z = 12 . . . (3)
From (2), x = -6 - 3y - 3z . . . (4)
Substituting for x in (1) and (3) gives
3(-6 - 3y - 3z) - y + z = 5 => -18 - 9y - 9z - y + z = 5 => -10y - 8z = 23 . . (5)
-6 - 3y - 3z + 4y - 2z = 12 => y - 5z = 18 . . . (6)
(6) x 10 => 10y - 50z = 180 . . . (7)
(5) + (7) => -58z = 203
z = 203/-58 = -3.5
From (6), y - 5(-3.5) = 18 => y = 18 - 17.5 = 0.5
From (4), x = -6 - 3(0.5) - 3(-3.5) = -6 - 1.5 + 10.5 = 3
x = 3, y = 0.5, z = -3.5
Negative exponents work like this:
![a^{-b}=\dfrac{1}{a^b}](https://tex.z-dn.net/?f=a%5E%7B-b%7D%3D%5Cdfrac%7B1%7D%7Ba%5Eb%7D)
So, in order to evaluate a negative exponent, you simply have to invert the base, and then raise to the positive equivalent of the exponent.
As an example, here are the first three exercises:
![8^{-3}=\dfrac{1}{8^3}=\dfrac{1}{512}](https://tex.z-dn.net/?f=8%5E%7B-3%7D%3D%5Cdfrac%7B1%7D%7B8%5E3%7D%3D%5Cdfrac%7B1%7D%7B512%7D)
![(-4)^{-5}=\dfrac{1}{(-4)^5}=-\dfrac{1}{1024}](https://tex.z-dn.net/?f=%28-4%29%5E%7B-5%7D%3D%5Cdfrac%7B1%7D%7B%28-4%29%5E5%7D%3D-%5Cdfrac%7B1%7D%7B1024%7D)
![2k^{-4}=\dfrac{2}{k^4}](https://tex.z-dn.net/?f=2k%5E%7B-4%7D%3D%5Cdfrac%7B2%7D%7Bk%5E4%7D)
You can work out the rest applying this logic.